A Novel Method for Analysis of Phosphine (PH3) Residues in Canola and Cottonseed - Xiao, Yu; Gu, Chunyuan; Yu, Jinghui; Shan, Changyao; Ren, Yonglin (Current Microwave Chemistry, 2018)
Background: Seeds are treated with phosphine (PH3) fumigant to protect them from insects while under storage. However, health concerns mean it is essential to quantify phosphine residues after fumigation. Residues are normally measured either after solvent extraction or purge and trap procedures, but there remain problems of solvent interference in measurements. Microwave irradiation is an excellent method to release PH3 from grain, but there are no reports of this being used on oilseeds. Methods: Three methods were compared to measure phosphine residues in canola and cottonseed: solvent extraction only, grinding plus solvent extraction, and microwave irradiation. The headspace concentration of PH3 was analysed by Gas Chromatography (GC) equipped with a Pulsed Flame Photometric Detector (PFPD). Completeness of microwave extraction was estimated from the amount of fumigant retained by the microwaved samples. This amount was determined by further microwave irradiation. Results: Recoveries of PH3 from fortified canola and cottonseed samples were 94.8±5.7% to 96.3±5.5% for the grinding plus solvent method and 95.8±6.1% to 96.4±7.1% for the microwave method. Quantitative results from microwave irradiation and the grinding plus solvent methods were similar. Yield from solvent extraction was 50% lower than that from the other methods tested. Completeness of microwave extraction was less than 5% of the amount obtained from the initial procedure. Limits of quantification were < 0.001 ng/g. Conclusion: The microwave method is rapid (<5 min per sample), solvent-free and requires only a small amount of sample.
Keywords: Canola and cottonseed